2005
DOI: 10.1111/j.1540-627x.2005.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Growth Cycle Theory of Small Firm Financing

Abstract: This paper empirically tests the financial growth cycle model for small and medium-sized enterprises (SMEs), which postulates that as firms become larger, older, and more informationally transparent, their financing options become more attractive. We add to the literature by providing one of the first empirical tests of the model using a large, cross-sectional data set. Our results partially support the financial growth cycle model. Specifically, our results show larger firms, as measured by total number of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(128 citation statements)
references
References 19 publications
7
106
0
15
Order By: Relevance
“…Les difficultés d'accès de la PME à la forte croissance sont fréquemment associées à des contraintes liées aux ressources financières (Hambrick et Crozier, 1985 ;Hutchinson et Ray, 1986 ;Westhead et Storey, 1997 ;Becchetti et Trovato, 2002 ;Wiklund et Shepherd, 2003 ;Gregory et al, 2005). Le phénomène de forte croissance aurait en effet tendance à amplifier « la pénurie financière » que doivent surmonter les PME (Saint-Pierre, 2005).…”
Section: La Forte Croissance La Problématique Des Ressources Financiunclassified
“…Les difficultés d'accès de la PME à la forte croissance sont fréquemment associées à des contraintes liées aux ressources financières (Hambrick et Crozier, 1985 ;Hutchinson et Ray, 1986 ;Westhead et Storey, 1997 ;Becchetti et Trovato, 2002 ;Wiklund et Shepherd, 2003 ;Gregory et al, 2005). Le phénomène de forte croissance aurait en effet tendance à amplifier « la pénurie financière » que doivent surmonter les PME (Saint-Pierre, 2005).…”
Section: La Forte Croissance La Problématique Des Ressources Financiunclassified
“…De plus, des théories spécifiques ont été développées comme la théorie de Revue internationale P.M.E., vol. 24, n os 3-4, 2011 l'ordre hiérarchique (pecking order theory), les théories de l'endettement parmi lesquelles celles fondées sur les actifs (asset based lending theory) ou sur les partenariats (relationship lending theory) et, enfin, la théorie du cycle de vie financier (Berger et Udell, 1998 ;Fluck, Holtz-Eakin et Rosen, 1998 ;Gregory, Rutherford, Oswald et Gardiner, 2005).…”
Section: éMergence D'un Corpus Théorique De La Finance Entrepreneurialeunclassified
“…Robb and Wolken (2002) found that bigger, mature firms were more likely to have arrearage than smaller firms. Gregory et al (2005) found that younger firms are more likely to use long-term debt. In Nigeria, SMEs is constrained in obtaining external from lenders, and they are generally required to pledge assets of the business or owners.…”
Section: Size -mentioning
confidence: 99%
“…Empirical studies show that the age of the firm is an important factor influencing the firm in sourcing for the choice of financing. Gregory, Rutherford, Oswald, and Gardiner (2005); Mac an Lucey (2010, 2011) argued that age together with experience and transparency play positive role in gaining access to public equity or long-term debt financing. They also assert that when lending to small firms, financial institutions require owners to pledge personal assets to guarantee payback of the loan.…”
Section: Size -mentioning
confidence: 99%